PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN KELUARGA DI INDONESIA - Adhitya Rechandy Christian Santoso (Jurnal Fokus Manajemen Bisnis, 2020)
This study discusses the application of corporate governance to the performance of family companies in Indonesia. The relationship of corporate governance in this study was proxied with an independent board of commissioners, the size of the board of directors, and the size of the audit board. The measurement of the financial performance of this study uses Return On Assets (ROA) with a sample of research companies listed on the Indonesia Stock Exchange in the 2014-2018 period.The sampling method in this study uses purposive sampling and data analysis using multiple linear regression with the help of SPSS 21.The results of data analysis, the proportion of independent commissioners and the size of the board of directors had a significant positive effect on the variable size of the audit board not having a significant effect.